2009
DOI: 10.1371/journal.pone.0007635
|View full text |Cite
|
Sign up to set email alerts
|

Stringency of the 2-His–1-Asp Active-Site Motif in Prolyl 4-Hydroxylase

Abstract: The non-heme iron(II) dioxygenase family of enzymes contain a common 2-His–1-carboxylate iron-binding motif. These enzymes catalyze a wide variety of oxidative reactions, such as the hydroxylation of aliphatic C–H bonds. Prolyl 4-hydroxylase (P4H) is an α-ketoglutarate-dependent iron(II) dioxygenase that catalyzes the post-translational hydroxylation of proline residues in protocollagen strands, stabilizing the ensuing triple helix. Human P4H residues His412, Asp414, and His483 have been identified as an iron-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
0
28
0
1
Order By: Relevance
“…The iron is bound in the active site by two histidine residues and an aspartate residue. The spatial orientation of these three residues around the iron is not known in P4H, though that orientation is critical for enzymatic activity (Gorres et al , 2009). This 2-His–1-carboxylate motif is common to the α-ketoglutarate-dependent, iron(II) dioxygenases.…”
Section: Prolyl 4-hydroxylasementioning
confidence: 99%
See 1 more Smart Citation
“…The iron is bound in the active site by two histidine residues and an aspartate residue. The spatial orientation of these three residues around the iron is not known in P4H, though that orientation is critical for enzymatic activity (Gorres et al , 2009). This 2-His–1-carboxylate motif is common to the α-ketoglutarate-dependent, iron(II) dioxygenases.…”
Section: Prolyl 4-hydroxylasementioning
confidence: 99%
“…In the halogenases, the carboxylate (Asp or Glu) is replaced by an alanine residue and a halide ion. Simply replacing the active-site Asp of human P4H with an alanine residue does not, however, endow the enzyme with halogenase activity (Gorres et al , 2009). Overall, the α-ketoglutarate-dependent dioxygenases show low sequence identity, but do share a common three-dimensional structural fold.…”
Section: Protein Structurementioning
confidence: 99%
“…To further reinforce this notion, simple substitution of coordinating Asp to Ala on prolyl 4-hydroxylase, an Fe/αKG enzyme, led to an inactive enzyme. 65 Thus, despite the presumed evolutionary relationship between the two enzymes, the simplistic notion of creating a vacant coordination site for halide binding to convert a hydroxylase to halogenase only works in very special cases.…”
Section: New Opportunities On the Horizon?mentioning
confidence: 99%
“…Isothermal titration calorimetry analysis suggested that Ni (II) binds to ABH2 with higher affinity than Fe (II). It is likely that dioxygenases such as PHD family, JmjC-domain containing histone demethylases and ABH DNA repair enzymes use the same iron coordinating motif (His-Asp-His) to bind ferrous iron at their active sites, and Ni(II) competes with Fe(II) and replaces it at the iron-binding site (Chen et al 2010a; Gorres et al 2009). …”
Section: Iron Homeostasis and Dioxygenase Activitymentioning
confidence: 99%